2018
DOI: 10.1016/j.ijid.2018.04.3951
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of HCV care among HIV/HCV coinfected patients

Abstract: Background: Due to overlap ways of transmission, HIV and hepatitis C (HCV) co-infection is highly prevalent. The aim of this study was to characterize the HCV cascade of care among HIV/HCV infected individuals in a major HIV center in Buenos Aires, Argentina.Methods & Materials: Data was drawn from Electronic Medical Records of HIV/HCV co-infected individuals. We assessed the number and proportion of patients achieving each step of the HCV cascade: RNA confirmation, fibrosis staging, treatment initiation, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The HBV co-infection rate of 8% in our study is within this range and is consistent with the proportions found in other studies in the Asia-Pacific region [20,31]. Similarly, the HCV co-infection rate of 9% is also within the global estimates of 2%-15% of PLHIV with HCV co-infection [32,33]. Increased or routine VH screening would allow a higher proportion of patients with HBV and HCV to be diagnosed and treated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The HBV co-infection rate of 8% in our study is within this range and is consistent with the proportions found in other studies in the Asia-Pacific region [20,31]. Similarly, the HCV co-infection rate of 9% is also within the global estimates of 2%-15% of PLHIV with HCV co-infection [32,33]. Increased or routine VH screening would allow a higher proportion of patients with HBV and HCV to be diagnosed and treated.…”
Section: Discussionsupporting
confidence: 91%
“…The HCV CoC found that 51% of those tested for HCV RNA had active HCV viremia. With the majority of HCV cases being primary and very few re‐infections identified, this proportion is low compared with other studies, which have found higher proportions of confirmed HCV viremia [30,33]. Since it is common for clinics and laboratory testing centres in the region not to be linked, this low proportion may be due to delays in clinics receiving results.…”
Section: Discussionmentioning
confidence: 79%